Prevention of exertional lower body musculoskeletal injury in tactical populations: protocol for a systematic review and planned meta-analysis of prospective studies from 1955 to 2018 - Flanagan, Shawn D. (Syst Rev, 2018)
BACKGROUND: Exertional lower body musculoskeletal injuries (ELBI) cost billions of dollars and compromise the readiness and job performance of military service and public safety workers (i.e., tactical populations). The prevalence and burden of such injuries underscores the importance of prevention efforts during activities necessary to sustain core occupational competencies. Attempts to synthesize prevention techniques specific to tactical populations have provided limited insight on the comparative efficacy of interventions that do not modify physical training practices. There is also a need to assess the influence of sex, exposure, injury classification scheme, and study design. Thus, the primary purpose of the systematic review and planned meta-analysis detailed in this protocol is to evaluate the comparative efficacy of ELBI prevention strategies in tactical populations. METHODS: A systematic search strategy will be implemented in MEDLINE, EMBASE, Cochrane, and CINAHL. A multi-tiered process will be used to capture randomized controlled trials and prospective cohort studies that directly assess the prevention of ELBI in tactical population(s). Extracted data will be used to compare prevention strategies and assess the influence of heterogeneity related to occupation, sex, exposure, injury characteristics, and study quality. In addition, individual risk of bias, meta-bias, and the quality of the body of evidence will be rigorously tested. DISCUSSION: This systematic review and planned meta-analysis will comprehensively evaluate ELBI mitigation strategies in tactical populations, elucidate factors that influence responses to treatment, and assess the overall quality of the body of research. Results of this work will guide the prioritization of ELBI prevention strategies and direct future research efforts, with direct relevance to tactical, health and rehabilitation science, and human performance optimization stakeholders. SYSTEMATIC REVIEW REGISTRATION: The systematic review protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO) on 3 Jan 2018 (registration number CRD42018081799). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13643-018-0730-9) contains supplementary material, which is available to authorized users.